2018
DOI: 10.3390/w10111622
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Relationship between Drought and Water Scarcity Using Copulas: Case Study of Beijing–Tianjin–Hebei Metropolitan Areas in China

Abstract: Making the distinction between drought and water scarcity is not trivial, because they often occur simultaneously. In this study, we used Copulas to quantify the relationship between drought and water scarcity. Beijing–Tianjin–Hebei Metropolitan Areas (BTHMA) was chosen as the study area. Standard Precipitation and Evapotranspiration Index (SPEI) and water exploitation index plus (WEI+) was chosen to represent metrological drought and water scarcity. Inverse Distance Weighted method was used for spatial analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The commonly used bivariate theoretical Copula functions include Normal-copula, t-copula, Clayton-copula, Frank-copula, and Gumbel-copula. Based on the extracted two characteristic variables of drought duration and severity, the empirical joint distribution function of the theoretical Copula function was fitted respectively, and the goodness of fit (GOF) of the Copula joint distribution function was tested based on the square Euclidean distance (d 2 ), Akaike Information Criterion (AIC), and root mean square error (RMSE) [47]. Copula families used in this research are shown in Table 2.…”
Section: Name Cumulative Distribution Function (Cdf)mentioning
confidence: 99%
“…The commonly used bivariate theoretical Copula functions include Normal-copula, t-copula, Clayton-copula, Frank-copula, and Gumbel-copula. Based on the extracted two characteristic variables of drought duration and severity, the empirical joint distribution function of the theoretical Copula function was fitted respectively, and the goodness of fit (GOF) of the Copula joint distribution function was tested based on the square Euclidean distance (d 2 ), Akaike Information Criterion (AIC), and root mean square error (RMSE) [47]. Copula families used in this research are shown in Table 2.…”
Section: Name Cumulative Distribution Function (Cdf)mentioning
confidence: 99%
“…Several methods have been proposed to investigate the bivariate characteristic of droughts, such as the product of the conditional distribution of drought severity for a given drought duration and the marginal distribution of drought duration to construct the joint distribution of drought duration and magnitude used by Salas et al [73] and González and Valdés [74], with complex mathematical derivation involved. Nevertheless, multivariate distributions using copulas, whose applications in hydrology have been increasing in recent years with several and different uses [67,[75][76][77][78][79][80], can overcome such issues.…”
Section: Bivariate Analysis Of Drought Duration and Magnitudementioning
confidence: 99%
“…Major research results include: De Michele (2005) used the 2D copula function to calculate the designed flood yield of dams, and Salvadori (2006) used the 2D copula function to study the statistical characteristics of storms at sea [6,7]. De Michele (2013) and Linlin (2018) applied copula functions to analyze the drought frequency and its recurrence interval [8,9]. Razmkhah (2016) [10] and Yan (2018) [11] used the 2D copula function to study the relationship between precipitation and runoff.…”
Section: Introductionmentioning
confidence: 99%